Applying livestock thresholds to examine poverty in Karamoja - Andy Catley (SpringerOpen, 2021)
Abstract In pastoralist and agro-pastoralist areas, wealth and poverty are closely aligned to levels of livestock ownership and social inclusion. Whereas cash income per capita is a useful measure of poverty in non-pastoralist areas, measures of livestock ownership per capita are needed to understand poverty in pastoralist systems. This study estimated a livestock threshold for agro-pastoralist households in Karamoja, being the minimum per capita ownership of livestock needed to sustain a predominantly agro-pastoral livelihood. The study then applied the livestock threshold to pre-existing livestock population data to estimate the proportions of households above and below the threshold. Using an estimated livestock threshold of 3.3 Tropical Livestock Units (TLU)/capita for agro-pastoralism, 56.5% of households in Karamoja’s main livestock-keeping districts were below the threshold and could be categorized as livestock-poor. The ownership of livestock was skewed in two main ways. First, there was a high-end skew with the wealthiest 30% of households owning 69.3% of all livestock in terms of TLU. Second, there was a low-end skew. Among poorer households, below the 3.3 TLU/capita livestock threshold, livestock ownership was skewed away from the threshold. Forty-seven per cent of these households owned only 1.2 TLU/capita or less; 13% of households owned no livestock at all. These findings are discussed, with programming and policy recommendations.